The Attentional Boost Effect in Older Adults: Examining the Vulnerable Boost Hypothesis. - Spataro, Pietro; Prull, Matthew W.; Santirocchi, Alessandro; Rossi-Arnaud, Clelia (Experimental Aging Research)
Introduction: The Attentional Boost Effect (ABE) occurs whenever participants recognize stimuli paired earlier with to-be-responded targets better than stimuli earlier paired with to-be-ignored distractors or presented on their own (baseline). Previous studies showed that the ABE does not occur in older adults when the encoding time is too short (500 ms/word) or when encoding is incidental, likely due to aging-related reductions in cognitive resources or limitations of processing speed. Method: In the present study, younger and older adults encoded words presented for 1000 ms under intentional instructions. In addition, to determine the potential impact of the retention interval, the recognition task was performed after a delay of 2 minutes (Experiment 1) or 20 minutes (Experiment 2). Results: Under these conditions, older adults showed a significant ABE and the size of the effect was comparable to that achieved by younger adults. The magnitude of the ABE was vulnerable to the passage of time because the recognition advantage of target-paired words decreased sharply from 2 to 20 minutes. Conclusions: Taken together, our data demonstrate that younger and older adults may have comparable ABE effects under specific conditions and are similarly sensitive to interference.